2023
DOI: 10.1002/cam4.6559
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the risk of myasthenia gravis related to immune checkpoint inhibitors based on the US FDA Adverse Event Reporting System

Qingli Kong,
Hui Wang,
Xiaolei Ren
et al.

Abstract: ObjectiveTo evaluate the risk of myasthenia gravis (MG) associated with immune checkpoint inhibitors (ICI).MethodsAdverse event (AE) reports related to MG, myasthenic syndrome, and MG crisis for durvalumab, atezolizumab, pembrolizumab, nivolumab, avelumab, and ipilimumab in the US FDA Adverse Event Reporting System (FAERS) from Q1 2004 to Q3 2022 were collected. The proportional reporting odds ratio (PRR) method was used to evaluate the correlation between the six drugs and the three AEs. Statistical significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A further case study described a patient who developed encephalitis and neuropathy following treatment with nivolumab and atezolizumab, with paresthesia persisting to the end of treatment [ 26 ]. Myasthenia gravis has been shown to occur following induction of atezolizumab, and a pharmacovigilance study found 78 cases, with 34% resulting in death [ 27 ]. Guillain–Barré syndrome is a rare outcome following ICI use, though a study from the FAERS database found that ICI monotherapy was associated with the condition, as well as myasthenia gravis, encephalitis, myelitis, meningitis, and neuropathy, which agrees with our findings [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further case study described a patient who developed encephalitis and neuropathy following treatment with nivolumab and atezolizumab, with paresthesia persisting to the end of treatment [ 26 ]. Myasthenia gravis has been shown to occur following induction of atezolizumab, and a pharmacovigilance study found 78 cases, with 34% resulting in death [ 27 ]. Guillain–Barré syndrome is a rare outcome following ICI use, though a study from the FAERS database found that ICI monotherapy was associated with the condition, as well as myasthenia gravis, encephalitis, myelitis, meningitis, and neuropathy, which agrees with our findings [ 28 ].…”
Section: Discussionmentioning
confidence: 99%